The Influence of In-House Training Towards The Accuracy of Nursing Care Documentation - Felisitas A Sri S, Sr; Sutiyarsih, Emy (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Nursing documentation can be used as legal evidence if there are lawsuits. Therefore, nursing documentation must be done systematically and continuously. The aim of this study was to analyze the effect of in-house training about nursing care documentation to the accuracy of documenting nursing care at X hospital. This study was a quasi-experimental study with one group post-test design. The population of nurses at X hospital. The respondents were nurses that were randomly selected from all wards at X hospital. The ANOVA test was used for data analysis. The results of this study stated that there was a significant influence of in-house training on the accuracy of documentation of nursing care, with p-value = 0.000 < 0.05. In conclusion, the findings highlight that continuous training in nursing care process will be able to improve the quality of nursing care documentation. However, it is recommended to conduct an ongoing evaluation.